DAGESTAN REGION BETWEEN THE TWO REVOLUTIONS OF 1917 (BALANCE OF SOCIO-POLITICAL POWERS) - Salihova, Lejla Bagautdinovna; Aagan, Burkutbaj Gelmanovic (History, Archeology and Ethnography of the Caucasus, 2020)
The article discusses the distribution of socio-political powers in Dagestan region during the period of the February and October revolutions of 1917. The aim of the paper is to examine the process of formation of socio-political groups, to consider their opposition. The February events of 1917 in Petrograd led to the victory of the revolution. In this regard, a difficult situation arose in the Dagestan region: the victory led to a deterioration of the political situation, to demarcation within the opposing political forces. The paper highlights the formation of various political groups and government bodies which replaced tsarism. The study shows that the Provisional Regional Executive Committee and its district and local authorities, Councils of Soldiers and Officers (Workers) Deputies, religious communities, organizations belonging to one or another ethnic group, etc. were organized in the region. The authors point out the organization of the Provisional Regional Executive Committee, which became the body of power of the Provisional Government, to the opposition of the members of the committee itself, to the organization of Union of Allied Mountaineers of the North Caucasus and Dagestan, etc. The fact that representatives of socio-political groups took an active part in congresses and meetings held in the North Caucasus, Dagestan is noted. Analysis of the period under study demonstrates that the political situation in Dagestan was tense, however the struggle of opposing parties was carried out within the democratic principles. It mainly manifested itself in the struggle between the socialist group and representatives of N. Gotsinsky. When writing the paper, the works of domestic researchers was used, among which the works of contemporaries of revolutionary events.